Redesain Sekolah Alam Surya Mentari Surakarta - Sriyanto, Joko; , Nur Rahmawati, ST, MT; , Yayi Arsandrie, ST, MT (2016)
Education is a learning process that can produce changes in all respects, including behavior, attitudes and intellectual changes. Education is a process of learning to be better than ever. Education also aims to help reach maturity mindset and interact with their environment. Namely school buildings or institutions for learning and teaching as well as a place to receive and give lessons according tingkatanya. Nature School is a teaching and learning activities that use nature as the main teaching materials and has its own characteristics without deviating from the curriculum that applies nationally. Alam Surya Mentari Surakarta school is a school that is formed from the development of TK and Play Group Alam Surya Mentari which was founded in 2009 using the concept-based early education with nature. In the concept of the natural school there are several criteria, ie nature as a learning space, nature as media and teaching materials, and nature as an object lesson. Overall the school Alam Surya Mentari been nice, but still lacks a little in terms of natural lighting in classrooms for opening only one side of the classroom makes the lighting is uneven. Therefore, the authors want to plan and rebuild Sekolah Alam Surya Mentari the Sustainable and accessible by the public without compromising the quality of learning in the city of Surakarta.